Analisis Framing Pemberitaan Pemilu 2024 Oleh Mahkamah Konstitusi pada Media IDN Times dan KR Jogja - Mezy Mezy; Muhammad Thoyib Amali (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze how two Indonesian online media outlets, IDN Times and KR Jogja, framed news coverage of the 2024 election dispute handled by the Constitutional Court. Using Robert Entman’s framing analysis model, this research explores how each media constructs narratives, selects facts, and emphasizes certain issues to shape public perception. The findings reveal that IDN Times tends to present information in a neutral and procedural tone, focusing on legal processes and official statements. In contrast, KR Jogja emphasizes public skepticism and the discourse of electoral justice, using critical language choices and sources that question the fairness of the election. This contrast in media framing impacts how audiences perceive the credibility of the Constitutional Court and the broader legitimacy of Indonesia’s electoral democracy. The study highlights that media outlets are not passive conveyors of facts but active agents in constructing political realities. These findings contribute to the field of political communication and media literacy, especially in post-election contexts where public trust in democratic institutions is crucial. The research underscores the importance of critical media consumption and the role of framing in influencing democratic discourse in transitional political environments.